PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KETERLIBATAN KERJA TERHADAP KEPUASAN KERJA PADA PT PEGADAIAN CABANG KAROMBASAN MANADO - Kaunang, Laviola (JURNAL ADMINISTRASI BISNIS, 2026)
This study aims to analyze the influence of transformational leadership and job engagement on job satisfaction at PT Pegadaian Karombasan Manado Branch. Data were collected through questionnaires on 26 employees using census sampling techniques. The analysis was conducted using Partial Least Squares (SmartPLS 4.1.1.4). The results show: (1) transformational leadership has a significant positive effect on job engagement; (2) job engagement has a significant positive effect on job satisfaction; (3) transformational leadership does not have a direct effect on job satisfaction through job engagement. These findings confirm the importance of transformational leadership style in building job engagement, although the indirect effect on job satisfaction requires further attention in the environment of PT Pegadaian Karombasan Manado Branch.